Longino, Friday (2020).The Design of a Medical Clinic at Kabale University, Faculty of Engineering Technology, Applied Design and Fine Art. Kabale: Kabale University. - Longino, Friday (Kabale University, 2023)
This project helped us relate the theoretical work and the practical. The project was carried out at faculty of Engineering at it was aimed at designing a faculty medical clinic.